2016
DOI: 10.1016/j.jtho.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Analysis of Prognostic Factors in Patients with Unresectable Malignant Pleural Mesothelioma

Abstract: Introduction Previous prognostic scoring systems for MPM included patients managed surgically and predated the use of pemetrexed. We analyzed prognostic factors in a contemporary cohort of patients with unresectable MPM who received pemetrexed-based chemotherapy. Methods This single institution analysis included MPM patients managed non-surgically from 2000–2013. Variables correlated with overall survival (OS) included sex, performance status (PS), asbestos exposure, tumor laterality, histology, clinical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 14 publications
3
68
1
1
Order By: Relevance
“…This means that in the present study it was possible to prevent overoptimistic estimates of test performance and externally validate the prognostic utility of CAR. In this study, neither stage nor PS were a significant prognostic factor of OS, while a recent report regarding the prognostic factors in 191 patients with unresectable MPM showed that PS, but not stage, was an independent prognostic factor (25). Another previous study that included 274 patients with MPM also showed that PS, but not stage, was an independent prognostic factor (1).…”
Section: Discussioncontrasting
confidence: 64%
“…This means that in the present study it was possible to prevent overoptimistic estimates of test performance and externally validate the prognostic utility of CAR. In this study, neither stage nor PS were a significant prognostic factor of OS, while a recent report regarding the prognostic factors in 191 patients with unresectable MPM showed that PS, but not stage, was an independent prognostic factor (25). Another previous study that included 274 patients with MPM also showed that PS, but not stage, was an independent prognostic factor (1).…”
Section: Discussioncontrasting
confidence: 64%
“…[17] In a number of studies, mean survival has been reported to be 4-12 months in patients with nonepithelial histology. [15][16][17][18][19] The present study included 35 patients with epithelial histology and overall survival (p=0.682) and disease-free survival (p=0.617) were numerically higher, but not statistically significant, in comparison to patient groups with other histological types.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…4 Epithelioid subtype has a median survival of 14.8 months, not classified subtype, 13.9 months, biphasic subtype 9.1 months, and 4 Clinical variable such as weight loss, anemia, hypoalbuminemia and platelet count are also other poor prognostic factors. 5 Expression of programmed death ligand 1 (PD-L1) has been studied in several tumors as a prognostic biomarker. PD-L1 is an inhibitory ligand, which binds to the program-cell death-1 transmembrane protein expressed on T cells, B cells and NK cells.…”
Section: Introductionmentioning
confidence: 99%